Internalisasi Nilai Tri Hita Karana Dalam Pendidikan Karakter Bagi Peserta Didik Tunagrahita di SLB Negeri 1 Buleleng - Made Widiana; Ni Luh Gede Hadriani; I Nyoman Miarta Putra (Cetta: Jurnal Ilmu Pendidikan, 2026)
Character education is an essential component of special education because it emphasizes not only academic achievement but also the development of students' attitudes, values, and adaptive behaviors. For students with intellectual disabilities, character education requires contextual, adaptive, and culturally responsive approaches. This study aimed to analyze the process of Tri Hita Karana value internalization in character education for students with intellectual disabilities at SLB Negeri 1 Buleleng, Bali, identify the pedagogical strategies implemented, and examine their implications for students' character development. This research employed a qualitative case study design. Data were collected through observations, in-depth interviews, and document analysis involving 15 informants consisting of the principal, teachers, students with intellectual disabilities, and parents. Data were analyzed using an interactive model through data reduction, data display, and conclusion drawing, while trustworthiness was established through source and technique triangulation. The findings indicate that the internalization of Tri Hita Karana values is embedded in school culture through religious habituation, guided social interaction, teacher role modeling, and environmental care activities adapted to students' learning characteristics. The parahyangan dimension nurtures religious discipline and spiritual awareness, pawongan develops empathy, cooperation, and social adaptation through structured guidance, while palemahan strengthens environmental responsibility, independence, and adaptive life skills through routine environmental practices. These findings suggest that, within the context of this case study, Tri Hita Karana represents a meaningful Balinese local wisdom-based framework that contributes to the holistic character development of students with intellectual disabilities.